Application of Machine Learning Models to Predict Maximum Event Water Fractions in Streamflow - Sahraei, Amir; Chamorro, Alejandro; Kraft, Philipp; Breuer, Lutz (Frontiers in Water, 2021)
Abstract can be found in the revised manuscript.